(untitled) (Swiss Medical Weekly, 2010)
Questions under study: The aim of this study was (a) to estimate the cost of dementia in Switzerland, (b) to compare the average annual cost for people with dementia who live at home and those living in an institution and (c) to analyse how the average cost per person with dementia who lives at home increases with the severity of dementia. Methods: This prevalence-based cost-of-illness study from a societal perspective combined top-down and bottom-up approaches and included both direct and indirect costs of dementia. Cost estimations were based on Swiss national statistics and surveys, as well as international reviews and expert interviews. Results:The total annual cost of dementia amounted up to CHF 6.3 billion for the year 2007. Together, institutional and informal care accounted for over 90% of the cost. The average annual cost was estimated at CHF 55’300 per person with dementia who lives at home and at CHF 68’900 per person who lives in an institution. The cost per person living at home with severe dementia was nearly five times the cost per person with mild dementia. Conclusions:The present study indicates that dementia imposes a considerable economic burden on Swiss society. The cost of dementia is dominated by the costs of care. Diagnosis and treatment related costs are minor. These findings are consistent with contemporary international studies on the subject. The contribution of informal caregivers is substantial since they account for 44% of the total cost of dementia (based on market cost valuation). Given demographic developments in Switzerland, healthcare decision making should have an interest in securing this potential for the future.